Additive manufacturing of functionally graded Ti-Al structures by laser-based direct energy deposition. (August 2021) - Hotz, Hendrik; Zimmermann, Marco; Greco, Sebastian; Kirsch, Benjamin; Aurich, Jan C.
Abstract: Two different grading strategies were investigated when manufacturing functionally graded materials (FGMs) by means of laser-based direct energy deposition. The FGMs consist of the aluminum alloys AlMg3 and AlSi10Mg and the titanium alloy TiAl6V4. The transition between the materials was realized in one case by a step transition and in the other case by a graded transition. The local chemical composition, microstructure and mechanical properties in the transition areas were investigated by means of optical micrographs, backscatter electron images, energy dispersive x-ray spectroscopy, a ternary phase diagram and microhardness measurements. In the transition area between the aluminum and titanium alloys, there are several kinds of intermetallic phases in both FGMs. However, the embrittlement due to these intermetallic phases was much less pronounced in the FGM manufactured with step transition.